2015
DOI: 10.1007/s13277-015-4174-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of soluble receptor-binding cancer antigen expressed on SiSo cells and carcinoembryonic antigen in differentiating malignant from benign pleural effusion

Abstract: Diagnosis of malignant pleural effusion (MPE) remains a major clinical challenge. The aim of this study was to evaluate the diagnostic value of combined detection of receptor-binding cancer antigen expressed on SiSo cells (RCAS1) and carcinoembryonic antigen (CEA) in patients with MPE and benign pleural effusion (BPE). The serum and pleural fluid samples were collected from 53 patients diagnosed with MPE and 49 patients with BPE. Enzyme-linked immunosorbent assay was used to detect the concentration of RCAS1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The results also con rmed that the CEA concentration and positive rate of lung ADC were signi cantly higher than those of SCC and SCLC, which was consistent with the literature report. There are also many reports on the use of CEA in the differential diagnosis of pleural effusion [22,23]. The results of this study demonstrated that the CEA levels of serum and pleural effusion in MPE were signi cantly higher than those in BPE, which was basically consistent with the report [10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…The results also con rmed that the CEA concentration and positive rate of lung ADC were signi cantly higher than those of SCC and SCLC, which was consistent with the literature report. There are also many reports on the use of CEA in the differential diagnosis of pleural effusion [22,23]. The results of this study demonstrated that the CEA levels of serum and pleural effusion in MPE were signi cantly higher than those in BPE, which was basically consistent with the report [10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…The results also confirmed that the CEA concentration and positive rate of lung ADC were significantly higher than those of SCC and SCLC, which was consistent with the literature report. There are also many reports on the use of CEA in the differential diagnosis of pleural effusion [ 23 , 24 ]. The results of this study demonstrated that the CEA levels of serum and pleural effusion in MPE were significantly higher than those of BPE, which was basically consistent with the report [ 11 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the sensitive and early determination of CEA is essential in prognosis of the original carcinoma and clinical tumor diagnoses. To date, many techniques, including enzyme-linked immunosorbent assay, square wave voltammetry, differential pulse voltammetry, fluorescence, capillary electrophoresis-chemiluminescence, and electrochemiluminescence have been exploited for the trace determination of CEA. In comparison with conventional techniques, which often require highly expensive and complex equipment, skilled operators, and a considerable amount of time for sample pretreatment, electrochemical methods exhibit the advantages of simple instrumentation, high sensitivity, low cost, specific recognition, and fast response when applied to detect CEA …”
Section: Introductionmentioning
confidence: 99%